Increase supply or manage demand? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Charles Batchelor explaining how the traditional Indian concept of water as a community resource has been replaced by a system of private wells, so restricting the access of poorer people to water.